ROSE PETAL TELLIN SHELL IN PARTY DRESS WITH CORSAGE TECHNIQUE - Annisa Juliany; Winwin Wiana (Fesyen Perspektif, 2017)
Rose Petal Tellin Shell or also called Pink Tellin Shell with scientific name Tellina Lineata is a mollusca animal that lives in the sea. Rose Petal Tellin is a beautiful shell. The color of the shell is graded pink. The shape of the tellin shells is generally oval. Because of its beauty Rose Petal Tellin Shell provides inspiration to making of an evening party for teenager. Model of dress is a full circle skirt and there some accents on the arm. Center of interest is found on the chest with the application of  corsage garniture that resembles the form of tellin shells. In making the design by considering the model and color of the dress, character who wants performed in this dress is the impression of feminine, cheerful, and dinamic. The method used in making the scientific work is Project Based Learning, which is problem solving activity or finding alternative problem solving using project or activity as media.